2014
DOI: 10.1371/journal.pone.0105880
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Malnutrition and Associated Factors among School Aged Children in Rural and Urban Settings of Fogera and Libo Kemkem Districts, Ethiopia

Abstract: IntroductionLittle information is available on malnutrition-related factors among school-aged children ≥5 years in Ethiopia. This study describes the prevalence of stunting and thinness and their related factors in Libo Kemkem and Fogera, Amhara Regional State and assesses differences between urban and rural areas.MethodsIn this cross-sectional study, anthropometrics and individual and household characteristics data were collected from 886 children. Height-for-age z-score for stunting and body-mass-index-for-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
121
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(166 citation statements)
references
References 31 publications
31
121
13
1
Order By: Relevance
“…This finding is in agreement with the findings of the Ghana demographic and Health survey in children under-five years, which show higher proportion of underweight among rural children compared to those in urban areas [37]. Another study in Ethiopia [38] also found high proportion of malnutrition among rural school children compared to their urban counterparts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is in agreement with the findings of the Ghana demographic and Health survey in children under-five years, which show higher proportion of underweight among rural children compared to those in urban areas [37]. Another study in Ethiopia [38] also found high proportion of malnutrition among rural school children compared to their urban counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Appiah and Laar [32] in 2014 found the proportion of wasting and stunting to be 19.4% and 50.3% respectively in the Nkwanta South District of the Volta Region. Similarly, in 2013, over 40% of stunting and 20% of wasting were observed among school children in rural Ethiopia [38].…”
Section: Discussionmentioning
confidence: 97%
“…The magnitude of stunting in this study was comparable with the nationwide estimate (22%) for the same age group and reported in other studies in Ethiopia [15,20,33]. On the other hand, acute malnutrition as indicated by wasting was relatively low compared to the nationwide prevalence (23%) and other studies which could be due to a lesser drought and related nutritional insults in the study area compared to some areas of the country [20,34]. Stunting was higher among boys than girls (30 vs. 22%; p-value = 0.037); a similar finding to previous studies from Ethiopia and other countries [1,13,20].…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have been reported in Ethiopia and Kenya among school age children (Herrador et al, 2014;Mwaniki & Makokha, 2013). Younger age associated with stunting may be due to the fact that these SAC may have had little nutritional deficit during their pre-school age.…”
Section: Normal Deficit Oversupporting
confidence: 85%